2023
DOI: 10.1002/fee.2666
|View full text |Cite
|
Sign up to set email alerts
|

Webs of science: mentor networks influence women's integration into STEM fields

Abstract: Mentorship can be part of the solution to developing a more diverse global scientific workforce, but robust longitudinal evidence is limited. Developmental mentor network theory can advance our understanding of the impact of a wide range of mentors across social contexts by distinguishing between the content of mentorship support (eg career support) and the structural characteristics of an individual's mentor network (eg density of connections among mentors). We tested the influence of mentor network character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These differences in network characteristics likely point to differential access to resources and benefits. A recent study of undergraduate women found that those with larger, more close-knit networks had a greater sense of scientific identity and were more likely to continue onto graduate studies (Hernandez et al, 2023). By participating and supporting mentoring programs, within your institution or scientific society, we can all help early career scientists build and diversify their networks.…”
Section: Mentoringmentioning
confidence: 99%
“…These differences in network characteristics likely point to differential access to resources and benefits. A recent study of undergraduate women found that those with larger, more close-knit networks had a greater sense of scientific identity and were more likely to continue onto graduate studies (Hernandez et al, 2023). By participating and supporting mentoring programs, within your institution or scientific society, we can all help early career scientists build and diversify their networks.…”
Section: Mentoringmentioning
confidence: 99%
“…For early career scientists, conferences present unique opportunities to meet fellow scientists, access resources, and grow their networks 2004. The characteristics of one's network determines access to information, opportunities, and resources (Hernandez et al 2023). An analysis of AGU Fall Meeting presentation abstracts from 2014-2018, illustrated that men's and women's networks, as defined by co-authorship, were inherently different.…”
Section: Manuscript Acceptance Data 2012-2021mentioning
confidence: 99%
“…These differences in network characteristics likely point to differential access to resources and benefits. A recent study of undergraduate women found that those with larger, more close-knit networks had a greater sense of scientific identity and were more likely to continue onto graduate studies (Hernandez et al 2023).…”
Section: Manuscript Acceptance Data 2012-2021mentioning
confidence: 99%